Strengthening Family Planning with Community-based Nutrition Interventions in Ethiopia : A Qualitative Study - Sellen, Daniel; Sharif, Sharmin; Tefera, Bethlehem; Hyder, Ziauddin (World Bank, Washington, DC, 2013)
A small-scale, exploratory, and qualitative operational research study was conducted in early 2011 to capture and examine stakeholder perspectives on integrated family planning (FP) programs implemented through Ethiopia's health extension program (HEP). Qualitative indications are that various stakeholders on both the supply and the demand side perceive that specific community-based nutrition (CBN) activities also delivered within HEP serve to link nutrition, family planning, and other health issues in socially acceptable and qualitatively effective ways. Remarkable concordance of qualitative indicators of service delivery, uptake, and satisfaction was noted on both the supply and demand side of service delivery at the sites studied. Respondent reports suggested the following: (i) active and successful delivery of both CBN and FP activities; (ii) some challenges with record keeping, supervision, and supplies; (iii) strong uptake of services and messages; (iv) a highly positive community-level perception of service quality, even in a partially capacitated kebele (neighborhood); and (v) an engaged response by participants. Qualitative indicators of community-level HEP staff, volunteer performance, and community satisfaction were generally positive. However, gaps and challenges to improving integration and delivery of FP and CBN within HEPs and in achieving sustainability in scale-up of integrated programs include (i) increasing capacity to support implant removal, (ii) maintaining human resources for health within the health extension program, and (iii) addressing the needs of youth in general and out-of-school youth in particular. Recommendations for improved delivery of integrated FP and CBN programs are to explore ways to (i) step up planning and resourcing for contraceptive implant removal, (ii) reduce staff turnover at the health posts and health centers, (iii) strengthen integrative supportive supervision and management of CBN, (iv) enhance recruitment and training of youth as health workers, (v) target adolescents and out-of-school youth for FP and CBN, (vi) harmonize integrated FP and CBN messaging, (vii) harmonize donor support for integration, and (viii) measure the effectiveness of integration.